PERANAN CENDAWAN MIKORIZA ARBUSKULAR DALAMMENINGKATKAN DAYA ADAPTASI BIBIT KELAPA SAWITTERHADAP CEKAMAN KEKERINGAN PADA MEDIA TANAHGAMBUT - Elis Kartika (Bioplantae, 2012)
In a long dried season, oil palm plant that planted in peat soil will hindered by drought stress. Drought stress is one of the main limiting factors in growth, nutrient uptake and yield of oil palm. One of the alternatives to overcome this drought stress problem on many plants is through inoculation with AMF. This research was conducted to observe the adaptability of oil palm seedling inoculated with AMF on drought stress in peat of used forest soil. The experiment on this soil type was arranged in a Factorial Completely Randomized Design with two factors. The first factor was AMF inoculation (M0= without AMF and M1 = inoculation of AMF) and the second factor was drought stress levels (available water 100%, 75%, 50% and 25%). Research result indicates that AMF inoculation improved the adaptability of oil palm seedling on every level of drought stress, as shown by the responses of growth and nutrient uptake. The adaptation of non-inoculated seedling on drought stress was solely by tolerance mechanism, either osmoregulation as shown by higher production level of osmoticum components or cell turgor regulation by leaf ABA accumulation. On the inoculated seedlings, however, there were synergism between those two tolerance mechanism and escape mechanism. Two important escape mechanisms were intensifying root system and decreasing transpiration surface of seedlings. Key words : oil palm, AMF, drought stress, adaptation mechanism